The metaphoric motivation of the caused-motion construction: A case study of perception - Del Campo Martínez, Nuria (International Journal of English Studies, 2013)
This article addresses the caused-motion construction from the theoretical perspective of the Lexical Constructional Model (LCM). Within the LCM, the way in which lexical templates fuse with constructional templates is coerced by internal and external constraints. Internal constraints specify the conditions under which allow predicates to take part in a construction. External constraints take the form of high-level metaphoric and metonymic operations that affect lexical-constructional subsumption. This proposal makes use of the theoretical tools of the LCM with a view to exploring instantiations of the construction with verbs of perception. Apart from internal constraints, high-level metaphor will be found to play a prominent role in the construal of the examples under scrutiny. The study will suffice to point out that the semantics of the caused-motion construction needs to be understood with reference to the underlying metaphoric mappings.